GE_GERICHTE C/19811/2011 vom 23. April 2012 - GE Cour de justice (2012)
; EXÉCUTION(PROCÉDURE) ; ÉVACUATION(EN GÉNÉRAL) ; COMPÉTENCE RATIONE MATERIAE ; TITRE EXÉCUTOIRE | CPC.326.1 CPC.338 CPC.336 CPC.208